HUBUNGAN LAMA PERAWATAN PASIEN DENGAN MOTIVASI KEBUTUHAN SEKSUAL LAKI-LAKI USIA 21 - 55 TAHUN DI RUMAH SAKIT UMUM ISLAM KUSTATI SURAKARTA - Indriyas Setyawan; Sulastri Sulastri (Universitas Muhammadiyah Surakarta, 2008)
Sexuality is complex phenomena and related with another aspects like biology, interpersonal, and behavior. Based on the result of interview and questionnaires distribution from 10 productive woman, 2 of them answer. While 8 from 10 productive men respondent say that they still have desire in completing the sexual need. This research aimed to know the old care relation with the motivation of sexual need 21 to 55 years old in Islamic General Hospital Kustati of Surakarta. This research belongs to associative that is research that seeks the relation between one variable to another variables. Based on the result of the correlation test using Chi-Square (χ 2 ) known that value χ 2 account = 6,627 and χ 2 tabel = 5,991 with value ρ = 0,036 in significant level 0,05, because ρ < 0,05 so H0 is rejected and Ha is accepted. It can be said that there is significant relation between the care relationship with the motivation of sexual need of men between 21-55 years old in Islamic General Hospital Kustati of Surakarta. Patient who taking care in Islamic General Hospital Kustati of Surakarta, 53 respondent (73, 60%) respondent the time categorized medium, 55 respondent (76,46%) have good motivation of sexual need. The is significant relation between times taking care of men 21-55 years old in Islamic General Hospital Kustati of Surakarta